Millennials Becoming Mothers: A Study of Pregnancy and Postpartum Behavior in the Digital Age - Hikmah, Hikmah (Journal of Public Health Indonesian, 2025)
This study aims to analyze the behavior of millennial mothers in undergoing pregnancy and postpartum in the digital era, by highlighting the role of technology as a source of information as well as a space for social interaction. Using a descriptive qualitative approach, data was obtained through in-depth interviews, limited observations, and literature review, then analyzed with thematic techniques. The results of the study show that digital media is the main source of knowledge, a means of social support, as well as a stage for self-expression for millennial mothers. Access to digital information provides benefits in the form of increased health literacy and confidence, but also poses the risk of information overload and anxiety due to exposure to invalid information. Online support has been shown to increase emotional resilience, but it does not completely replace real support from spouses and families. Social media on the other hand presents motivation, but also psychological distress through social comparisons that can trigger postpartum depression. Socio-economic factors also determine the quality of access to information, with mothers from the upper middle class benefiting more from premium apps, while lower-middle class groups are vulnerable to misinformation. The novelty of this research lies in the integration of pregnancy and postpartum analysis in the framework of digital literacy, online social support, and mental health, thereby enriching the study of maternal health behavior in the digital era. These findings are expected to be the basis for the development of intervention strategies that are more effective, humane, and adaptive to the needs of the millennial generation.